Multianalytical Non-Invasive Characterization of ‘Mater Boni Consilii’ Iconography Oil Painting - Federica Valentini; Sara De Angelis; Livia Marinelli; Camilla Zaratti; Marcello Colapietro; Ombretta Tarquini; Andrea Macchia (Heritage, 2023)
This paper presents the results of non-invasive diagnostic investigations performed on the canvas oil painting depicting the Marian iconography “Mater Boni Consilii”. The painting, whose author and origin are unknown, was found in an old shop in Florence following the overflowing of the Arno River in 1966. In order to define the importance of the artwork, a multianalytical analysis was performed on the painting, using multispectral imaging, X-ray fluorescence (XRF), and Fourier Transform Infrared Spectroscopy (FTIR-ATR) for the definition of materials, with a particular focus on the identification of pigments. The results allowed for the drawing up of a color palette, composed mainly of ochre and earth pigments, cinnabar, lithopone, lead white, and ultramarine pigments. After cross-referencing the acquired information with other findings, it was possible to place the painting in the period between the end of the XIXth and the beginning of the XXth centuries.